Rescue procedure for left main bronchus obstruction after patent ductus arteriosus clipping: a case report - Yukiko Ban; Masakazu Abe (Surgical Case Reports, 2018)
Abstract Background Obstruction of the left main bronchus is a rare but life-threatening complication following the closure of patent ductus arteriosus by surgical clips. We report a successful rescue procedure for this complication in a premature infant. Case presentation A 24-week gestational age premature girl weighing 903 g underwent surgical clipping for patent ductus arteriosus at the age of 24 days after birth. Bronchoscopy revealed the left main bronchus obstruction due to the clip compression at 6 h later after the surgery. The patient underwent a rescue re-exploration for this serious complication. New clips were applied to both the intrapericardial and the aortic ends of the patent ductus arteriosus respectively. And then the previous clips, compressing the left main bronchus, were gently removed from the ductus without ductus injury through a re-thoracotomy. Conclusions Surgeons should be aware of the possible complication and take care not to place patent ductus arteriosus clips obliquely toward the bronchus.